The Comparison of Swear Words Between Balinese and French Speakers - Putu Aditya Maesa Putra; I Gede Budasi; Rima Andriani Sari (PT PUSTAKA CENDEKIA GROUP, 2026)
This study aims to compare swear words used by Balinese and French speakers in terms of their forms, functions, and references, as well as to identify similarities and differences between the two languages. This research employed a qualitative comparative analysis design. The data were obtained from semi-structured interviews with three native Balinese speakers and three native French speakers, supported by document analysis of relevant academic theses. The data were analyzed based on the linguistic forms, pragmatic functions, and reference categories of swear words. The findings show that swear words in both languages occur in the forms of words, phrases, and clauses. Balinese demonstrates greater structural diversity than French, particularly in monomorphemic and polymorphemic words. Morphologically, Balinese tends to use combinations of prefixes and suffixes, whereas French predominantly employs suffixation. Pragmatically, both languages share six functions: emotional expression, attracting attention, emphasis, aggression or provocation, social bonding, and humor. However, Balinese swear words tend to be more direct and interpersonal, while French swear words more frequently express situational emotions. In terms of references, both languages involve religion, sex and gender, excrement, animals, sexual activity, personal background, and mental illness, but reflect distinct cultural and sociolinguistic backgrounds. These findings demonstrate that swear words are not merely offensive expressions but also reflect cultural values, social relationships, and communication patterns.